Age-related Differences in Tumour Characteristics and Prognostic Factors for Disease Progression in Cutaneous Squamous Cell Carcinoma of the Head and Neck - Alet J.G. Leus; Marjolijn S. Haisma; Jorrit B. Terra; Gilles F.H. Diercks; Marloes S. van Kester; Gyorgy B. Halmos; Emöke Rácz; Boukje A.C. van Dijk; Boudewijn E.C. Plaat (Medical Journals Sweden, 2022)
Guidelines for cutaneous squamous cell carcinoma of the head and neck do not take the age of the patient into account, but instead assume equal tumour characteristics and prognostic factors for poor outcome in younger and elderly patients. The aim of this study was to compare tumour characteristics of younger (< 75 years) and elderly (≥ 75 years) patients and identify age-specific risk factors for progression of disease, comprising local recurrence, nodal metastasis and distant metastasis. Patient and tumour characteristics were compared using χ2 or Fisher's exact tests. Multivariable competing risk analyses were performed to compare risk factors for progression of disease, incorporating the risk of dying before developing progression of disease. A total of 672 patients with primary cutaneous squamous cell carcinoma of the head and neck were retrospectively included. Larger tumour diameter, worse differentiation grade and deeper invasion were observed in older patients. In elderly patients, but not in younger patients, tumour diameter ≥ 40 mm, moderate differentiation grade and an invasion depth ≥ 2 mm were independent risk factors for progression of disease.